Entre citoyens et institutions : une co-production d’un capital environnemental sur le territoire urbain ? - Frédéric Bally (Éditions en environnement VertigO, 2018)
Fighting at their level against climate change, and managing their space for the well-being of residents, cities are places where nature makes a come back, in a background of sustainability. The territory of Lyon is strongly engaged in these problematic and acts with a few citizens’ initiatives to places nature in the center of the city by practices like composting and collective gardening. This text presents the results of a study focused on these initiatives and the impacts they have at a local scale. This context is an occasion to show how associations, gardeners and collectivity produce different forms of environmental capital on the territory of Lyon.